Penerapan Dynamic Governance dalam Penyelenggaraan Kabupaten Layak Anak di Kabupaten Sinjai - Salman Salman (Social Science Academic, 2026)
This study aims to analyze the application of dynamic governance in the implementation of Child-Friendly Regencies/Cities (KLA) in Sinjai Regency. The focus of the study is directed at three main capabilities, namely thinking ahead, thinking again, and thinking across. The research uses a descriptive qualitative approach. The research data sources include primary data from in-depth interviews and observations on the UPTD PPA, the field of child and women's protection, the Children's Forum, and elements of society, and secondary data in the form of institutional documentation, case data of the UPTD PPA Sinjai Regency in 2017-2024, KLA regulations, and supporting documents for the implementation of KLA. The results show that thinking ahead has been seen through openness to regulatory changes and long-term decision-making, but it is still hampered by delays in the flow of information and uneven distribution of programs. Thinking again is carried out through routine evaluations and preventive action plans, but its effectiveness is still influenced by low community participation and increasing cases of violence against children. Thinking across can be seen through the use of SIMFONI PPA, the integration of five KLA clusters, hybrid field verification, and cross-sector collaboration, but access to innovation is not even in remote villages. This study concludes that the implementation of dynamic governance in Sinjai has grown, but it still requires strengthening policy communication, participatory evaluation, village-based risk maps, and equitable distribution of child protection innovations.